Hematological Side Effects Management of Paclitaxel - Carboplatin Chemotherapy in Lung Cancer - Kornelis Aribowo; Wiwi Monica Sari (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background:  Paclitaxel-carboplatin chemotherapy can cause hema-tological disorders. This regiment's hematological side effects include anemia, neutropenia, and thrombocytopenia. Data showed this regiment side effect occurs with grade iii/iv toxicity anemia, grade III/IV anemia by 41%, neutropenia (78%), and thrombocytopenia (41%). This hema-tological disorder occurs in bone marrow-producing areas due to chemotherapy. Each hematological disorder requires separate interven-tion.Case Presentation: A 54-year-old woman was diagnosed with a progressive disease of left lung adenocarcinoma (Exon 21 mutation) with TKI and received paclitaxel-carboplatin chemotherapy. The patient experienced side effects of anemia, neutropenia, and thrombocytopenia. Anemia was treated with PRC transfusion, neutropenia corrected with Filgrastim, and thrombocytopenia with platelet transfusion. Chemo-therapy was discontinued after five cycles because the Thrombo-cytopenia condition did not improve.Conclusion: Hematological parameters are essential in preparing for lung cancer chemotherapy. Uncorrectable hematological disorders lead to discontinuation of chemotherapy